Modules Based on Technological Pedagogical Content Knowledge to Improve Elementary Students' Science Domain - Faizal; Khoirunnisa; Hendra Budiono (Universitas Pendidikan Ganesha, 2023)
The use of teaching modules based on technological pedagogical content knowledge has not been used to the maximum because teachers are still focused only on the theory. The purpose of this research is to produce a teaching module based on TPACK in order to improve the science domain of elementary school students. This research approach is a mix method with the type of Research and Development using the ADDIE development model. The qualification test covers the level of validity and practicality. Data collection tools use validity and practicality lifts. The data in this study is both quantitative and qualitative. The product validation results showed a validation rate of 94.29% for high validity categories. As for the media validity rate of 96% for High validity Categories, the material validation of 98% for higher validity, and the language validation for 88.89% for the High Validity Category. The practicality rate of 85.72% for the Good Practical Category, the teacher's response to 82% of the category was very Practical and the student's reply to 89.44% of the Category was Very Practice. The results of the research show that the teaching module based on technological pedagogical content knowledge (TPACK) to improve the science domain of elementary school students deserves to be used in the learning process.